STRATEGIES FOR ANALYZING ACADEMIC TEXT (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article, Strategies for Analyzing Academic Texts, provides a comprehensive overview of methods for critically engaging with scholarly works. The author emphasizes the importance of carefully reading and evaluating texts, identifying key arguments, and assessing the quality of evidence and methodology used. A key strength of the article is its thorough discussion of how to place texts within their broader academic and intellectual contexts, allowing readers to understand the work’s significance in the field. Additionally, the article offers valuable strategies for reflecting on the text’s limitations and ethical considerations, ensuring a well-rounded analysis. This resource is particularly useful for students and researchers looking to enhance their analytical skills and engage more deeply with academic literature.